The moral problem is a Hume problem - Green Karen (Belgrade Philosophical Annual)
The moral problem, as articulated by Smith, arises out of the attempt to introduce the experimental method of reasoning into moral subjects, developed by Hume. This paper returns to Locke's earlier attempt to provide an empirically adequate account of morality and the debate his attempt generated. It argues that the seeds of a more adequate, naturalistic account of the metaphysics and epistemology of morals than that developed by either Locke or Hume can already be found in aspects of Locke's Essay and in the defence of his views published by Catharine Trotter Cockburn. Locke and Cockburn find a natural, intrinsically moral, human disposition in our tendency to judge the moral good or evil of persons or actions in the light of their conformity with a moral law. It is constitutive of our nature as social beings that we are endowed 'with a moral sense or conscience, that approves of virtuous actions, and disapproves the contrary. ' Moral laws are those prohibitions and obligations that benefit others and society as a whole. Thus, the question of natural, moral motivation is seen to be independent of the question of the objective grounds of moral truth. In virtue of our nature as social beings we are motivated to do what is approved of by other members of our society. Whether what is approved of by a society genuinely fosters the welfare of its members is an independent, a posteriori question that can only be answered through reasoned, empirically informed debate.